Genotoxic and antigenotoxic effects of organic extracts of mushroom Agaricus blazei Murrill on V79 cells - da Rosa Guterres, Zaira; Mantovani, Mário Sérgio; da Eira, Augusto Ferreira [UNESP]; Ribeiro, Lúcia Regina [UNESP]; Jordão, Berenice Quinzani (FapUNIFESP (SciELO), 2005)
Agaricus blazei Murrill, popularly known as the sun mushroom, is a native mushroom in SP, Brazil, that has been widely used in the treatment of cancer and many other pathologies in different parts of the world. A water-soluble protein-polysaccharide complex (1 → 6)β-D-glucan has been isolated from its fruiting body that showed immune-modulation activity. From organic extracts, linoleic acid has been isolated and determined to be the main substance with antimutagenic activity. Using both the micronucleus (MN) and comet (single cell microgel electrophoresis) assays, this study determined the genotoxic and antigenotoxic potential of A. blazei (AB) obtained from commercial sources or the following strains: a) strains AB 97/29 (young and sporulated phases); b) a mixture taken from AB 96/07, AB 96/09 and AB 97/ 11 strains; and c) commercial mushrooms from Londrina, PR and Piedade, SP, designated as AB PR and AB SP, respectively. The extracts from these mushrooms were isolated in chloroform:methanol (3:1) and used in vitro at three different concentrations. V79 cells (Chinese hamster lung cells) were exposed to the extracts under pre-, simultaneous and post-treatment conditions, combined with methyl methanesulfonate (MMS). Under the circumstances of this study, these organic extracts did not show any genotoxic or mutagenic effects, but did protect cells against the induction of micronuclei by MMS. Copyright by the Brazilian Society of Genetics.
Keywords: Agaricus blazei; Comet assay; Micronuclei; Mushroom extracts; V79 cells; Agaricus blazei extract; alcohol; chloroform; mesylic acid methyl ester; animal cell; cell protection; cell strain V 79; comet assay; controlled study; drug activity; drug effect; drug exposure; drug isolation; fungal strain; genotoxicity; in vitro study; micronucleus; mushroom; mutagenicity; nonhuman; Animalia; Basidiomycota; Cricetulus griseus